Nasal skin reconstruction: Time to rethink the reconstructive ladder?. Issue 3 (March 2022) - Veldhuizen, Inge J.; Brouwer, Philip; Aleisa, Abdullah; Kurtansky, Nicholas R.; Dusza, Stephen W.; Nehal, Kishwer S.; Hoogbergen, Maarten M.; van der Hulst, René R.W.J.; Lee, Erica H.
Abstract: Background: Nasal scarring can compromise aesthetics and function given its complex three-dimensional structure and central location. This study aimed to measure patients' satisfaction after reconstruction for nasal defects following Mohs micrographic surgery. Methods: Patients presenting with nasal nonmelanoma skin cancer at Memorial Sloan Kettering Cancer Center New York, USA and Catharina Hospital Eindhoven, Netherlands from April 2017 to November 2019 were asked to participate. Reconstruction type, complications, and patients satisfaction were assessed. Patients completed the FACE-Q Skin Cancer – Satisfaction with Facial Appearance scale (preoperative and 1-year postoperative) and the Appraisal of Scars scale (1-year postoperative). Results: A total of 128 patients completed the preand postoperative scales. There were 35 (27%) surgical defects repaired with primary closures, 71 (55.5%) with flaps, and 22 (17.2%) with full-thickness skin grafts (FTSG). Patients that underwent a flap or FTSG reconstruction had higher scar satisfaction scores than primary closures (p = 0.03). A trend was seen with patients following flap reconstructions scoring 7.8 points higher than primary closures and patients with upper nose defects scoring 6.4 points higher than lower nose defects. Males were significantly more satisfied than females. No significant difference was observed in the preoperative and postoperative facial appearance scores between the three groups (p = 0.39). Conclusion: Patients are more satisfied in the long term with their scars after flap reconstructions compared to primary closures. Therefore, nasal skin reconstruction may not follow the traditional reconstructive ladder and more complex approaches may lead to higher long-term scar satisfaction.